2008
DOI: 10.1021/om701154f
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Conjugated Dienes with a Triruthenium Hydrido Carbonyl Cluster: Synthesis and Reactivity of Trinuclear Derivatives Having an Edge-Bridging Allyl Ligand

Abstract: The reactions of the hydrido triruthenium complex [Ru 3 (µ-H)(µ 3 -κ 2 -HNNMe 2 )(CO) 9 ] (1; H 2 NNMe 2 ) 1,1-dimethylhydrazine) with conjugated dienes give trinuclear derivatives that contain edge-bridging allyl ligands. The isolated allyl products are [Ru 3 (µ-κ 3 -C 8 H 13 )(µ 3 -κ 2 -HNNMe 2 )(µ-CO) 2 (CO) 6 ] (2) from 1,3cyclooctadiene, [Ru 3 (µ-κ 3 -C 6 H 9 )(µ 3 -κ 2 -HNNMe 2 )(µ-CO) 2 (CO) 6 ] (4) from 1,3-cyclohexadiene, and [Ru 3 (µκ 3 -C 4 H 6 OMe)(µ 3 -κ 2 -HNNMe 2 )(µ-CO) 2 (CO) 6 ] (5) from cis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…The Ni−Ni distance of 2.415(1) Å is consistent with metal–metal bonding between the two d 9 centres . To the best of our knowledge, there is only one precedent (Ru) for a cod‐derived bridging η 3 ‐allyl‐type ligand, and very few dinuclear Ni complexes with bridging allyl‐type ligands have been reported . The unexpected dangling nature of both N donors in the N imine C NHC N amine ligand of 2 prompted us to react the bis‐imine imidazolium salt 3 with [Ni(cod) 2 ] with the aim to form a N imine C NHC N imine pincer [Eq.…”
Section: Figuresupporting
confidence: 53%
“…The Ni−Ni distance of 2.415(1) Å is consistent with metal–metal bonding between the two d 9 centres . To the best of our knowledge, there is only one precedent (Ru) for a cod‐derived bridging η 3 ‐allyl‐type ligand, and very few dinuclear Ni complexes with bridging allyl‐type ligands have been reported . The unexpected dangling nature of both N donors in the N imine C NHC N amine ligand of 2 prompted us to react the bis‐imine imidazolium salt 3 with [Ni(cod) 2 ] with the aim to form a N imine C NHC N imine pincer [Eq.…”
Section: Figuresupporting
confidence: 53%
“…[12c] TheNi À Ni distance of 2.415 1is consistent with metalmetal bonding between the two d 9 centres. [12a] To the best of our knowledge,t here is only one precedent (Ru) for ac odderived bridging h 3 -allyl-type ligand, [13] and very few dinuclear Ni complexes with bridging allyl-type ligands have been reported. [12] Theu nexpected dangling nature of both N donors in the N imine C NHC N amine ligand of 2 prompted us to react the bis-imine imidazolium salt 3 with [Ni(cod) 2 ]with the aim to form aN imine C NHC N imine pincer [Eq.…”
Section: Communicationsmentioning
confidence: 99%
“…In a recent work, studying the reactivity of compound 1 with conjugated dienes, we found that these unsaturated reagents afford allyl cluster derivatives in high yields (Scheme ) . This synthetic approach represents an interesting alternative to the use of alkynes having α-hydrogen atoms as precursors to allyl ligands, especially if the alkyne required to make a particular allyl cluster complex is unknown or difficult to obtain, as happens for cyclic alkynes.…”
Section: Introductionmentioning
confidence: 79%
“…Apart from those described in the above commented works, , triruthenium cluster complexes having organic allyl ligands of the type R 1 R 2 CCR 3 CR 4 R 5 (R n ≠ M) are very rare, the only examples being [Ru 3 (μ 3 -κ 2 -PPhCH 2 PPh 2 )(μ-κ 3 -C 3 H 5 )(CO) 8 ] and [Ru 3 (μ 3 -κ 5 -HabqCHCHCHR)(μ-CO) 2 (CO) 6 ] (H 2 abqH = 2-amino-7,8-benzoquinoline; R = H, CCSiMe 3 ), which contain edge-bridging allyl ligands. Quite a few ruthenium cluster complexes containing 1,3-dimetalated allyl ligands (MR 1 CCR 2 CR 3 M) are known .…”
Section: Introductionmentioning
confidence: 99%